Cloning of linear T-cell epitops of EG95 antigen of Echinococcus granulosus into pGEX4t1 vector and expression analysis by SDS-PAGE - Roghayeh Mesri; Majid Esmaelizad; Mmozhghan Ahmadzadeh; Somayeh Mohammadi; Seyed Abdolhamid Angaji; Zahra Yazdanpour; Seyedeh Fahimeh Mmir Haghghouy Jali (Journal of Fasa University of Medical Sciences, 2016)
Background & Objectives: Echinococcus granulosus causes a common disease between humans and animals that called hydatid cyst or hydatidosis. The recombinant EG95 vaccine based on cloning of the 25 KD oncospheral antigen-Eg95- in pGEX stimulated significant humoral and cellular immunity in sheep, but regarding the effect of TH1cell immunity against this parasite and the influence of the linear T-cell epitopes in stimulating this immunity, only the coding sequence of linear T Cell epitopes of EG95 was cloned in pGEX and analyzed it's expression to optimize the qualification of this available vaccine in this study.